2021
DOI: 10.1177/2333393621995814
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnographic Study of the Moral Experiences of Children with Cancer in New Delhi, India

Abstract: There is a paucity of research examining children’s experiences with cancer in India. Childhood ethics is an emerging field, focusing on the moral dimension of children’s experiences, to promote children’s participation in their health care. A focused ethnography, using a moral experience framework, was conducted to better understand children’s participation in decisions, discussions, and actions in three oncology settings in New Delhi, India. We interviewed key informants, retrieved key documents, and conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Conversely, communication barriers and/or forgone meaningful encounters by HCPs may impede children’s agency and desired participation in care, contributing to negative moral experiences and feelings of frustration, anger, and fear. Other chronically-ill children expressed similar feelings as their involvement in care was heavily influenced by their illness severity, 48 HCP’s perceptions of their competency or need for “protection,” 19 , 20 and cultural or religious beliefs. 19 Participation in care is crucial for children’s long-term health as persistent marginalization can impede the development of self-management skills (e.g., health knowledge, communication skills, and healthcare system navigation) 49 and transition into adult healthcare systems, 50 which is a common concern in children with OI.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Conversely, communication barriers and/or forgone meaningful encounters by HCPs may impede children’s agency and desired participation in care, contributing to negative moral experiences and feelings of frustration, anger, and fear. Other chronically-ill children expressed similar feelings as their involvement in care was heavily influenced by their illness severity, 48 HCP’s perceptions of their competency or need for “protection,” 19 , 20 and cultural or religious beliefs. 19 Participation in care is crucial for children’s long-term health as persistent marginalization can impede the development of self-management skills (e.g., health knowledge, communication skills, and healthcare system navigation) 49 and transition into adult healthcare systems, 50 which is a common concern in children with OI.…”
Section: Discussionmentioning
confidence: 93%
“…The marginalization of children in their care appears to be a common issue within diverse healthcare settings and amongst children with various health conditions, such as (but not limited to) children hospitalized for planned treatment or acute illness, 17 , 18 as well as children with cancer 19 , 20 or cystic fibrosis. 21 , 22 For example, Coyne et al 20 found the input of children with cancer were rarely elicited in decisions regarding their health, leading to feelings of anger, anxiety, and frustration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations made during our study also supported the value of priming parents before delivering bad news. Previous research carried out in India showed that children with cancer had variable degrees of understanding about their disease but were almost always excluded from the decision-making [ 21 ]. Observations made during our study revealed that children may listen to the communication between adults even if the communication was not directed at them.…”
Section: Discussionmentioning
confidence: 99%
“…This approach focuses on how morally significant practices affect individuals’ everyday lives as well as the subjective and contextualized nature of people's experiences and the meanings ascribed to them (Carnevale et al, 2006; Hunt & Carnevale, 2011). This framework has been used to deeply understand what is valuable to children, including children living with disabilities, immigrant children in Montreal, children with cancer in India and the experiences of children in formal programming for mental health concerns – to name a few examples (Behan et al, 2021; Kooiman et al, 2012; Hunt & Carnevale, 2012; Montreuil, Noronha, Floriani, et al, 2018; Montreuil et al, 2017; Montreuil, Thibeault, McHarg, et al, 2018, Hunt and Carnevale, 2012). The goal of this study was to better understand the moral experiences of Indigenous children within an Anishinaabeg community.…”
Section: Introductionmentioning
confidence: 99%